Gluteal augmentation in post-massive weight loss patients - Mendes, Flavio Henrique [UNESP]; Viterbo, Fausto [UNESP] (Springer Nature, 2021)
Surgical treatment of obesity and its comorbidities has not only been recognized as one of the greatest achievements of modern medicine, but it also has created new body contour deformities for which our specialty has been devoted to correct in the last decades. Massive weight loss patients usually present with body contour deformities that often affect gluteal aesthetics. The lack of volume and projection is related to a severe disarrangement of the buttocks' frame, which requires specific measures to restore anatomical landmarks and to enhance shape and contour of the gluteal region. In most cases, circumferential body lift will be the first step to readjust the gluteal frame. Augmentation techniques such as fat grafting, autologous flaps, and alloplastic implants can be associated to enhance buttocks projection. Fat grafting helps restore volume and projection to the massive weight loss (MWL) buttocks, targeting different aesthetic units and globally promoting a true refill of the deflated subcutaneous spaces. Besides volume restoration, other regenerative and angiogenic properties of adipose tissue may be responsible for metabolic turnover and improvement in skin quality. Dermal flaps and silicone implants also contribute to increase buttock projection in specific gluteal units. As we continue to advance in our understanding of the MWL deformities, surgical techniques for gluteal contour will certainly be refined toward improving aesthetic outcomes and fewer complications.
Keywords: Belt lipectomy; Circumferential body lift; Gluteal augmentation; Gluteal fat grafting; Gluteal lift; Lower body lift; Massive weight loss; Postbariatric surgery